Two Week, OCT-Based follow-up as Guidance for Retreatment with Ranibizumab for CNV Apparently Refractory to Therapy. Issue 3 (May 2015) - Manousaridis, Kleanthis; Talks, James
Purpose: To assess the value of 2-week optical coherence tomography (OCT) follow-up for re-treatment decision-making in patients receiving monthly ranibizumab injections for choroidal neovascular membrane (CNV), which was apparently refractory to treatment. Methods: A total of 25 eyes of 25 consecutive patients with refractory CNV were included. Patients were classified as having refractory disease if no visual acuity (VA) change and no change in the pattern of macular fluid was noticed on OCT after at least 3 consecutive monthly injections, excluding the loading doses. Repeat injection was given and reassessment with VA and OCT was undertaken at 2, 4, 8, and 12 weeks. Results: Complete resolution or marked reduction of macular fluid was noted in 19 patients at 2 weeks (responders). In 18 responders, the fluid increased on 4- and persisted on 8- and 12-week follow-ups, so that further injections were given at these time points. In 6 patients, no significant change was noted at 2 weeks (nonresponders). In all of them, VA and OCT were stable on 4-, 8-, and 12-week follow-ups, without further injections. Conclusions: As some patients are responding for at least part of the month, injections may be worth continuing or possibly more frequent injections, tailored to the individual's response, may need to be considered. Alternative therapies such as aflibercept may also need to be considered. In nonresponding eyes, other cytokines except for vascular endothelial growth factor are probably involved in the pathogenesis or such cases may have structural damage that will not respond to therapy.